The Impact of Constructivist Learning Models on Student Achievement - Primarni, Amie; Tan, Ethan; Rosidin, Rosidin (Journal International Inspire Education Technology, 2025)
The traditional learning approaches prevalent in education often emphasize passive knowledge acquisition, leading to limited student engagement and lower academic achievement. Recognizing these challenges, this study investigates the impact of constructivist learning models on enhancing student achievement. The research aims to evaluate whether implementing constructivist strategies significantly influences students’ academic performance compared to conventional instructional methods. Employing a quasi-experimental design with pre-test and post-test control groups, the study involved 120 high school students selected through purposive sampling. Data collection was carried out using standardized achievement tests and observational checklists, analyzed quantitatively through descriptive and inferential statistics. Results indicate that students exposed to constructivist learning environments showed significantly higher academic achievements and increased active participation compared to their counterparts experiencing traditional instruction. In conclusion, the constructivist learning model effectively fosters critical thinking, enhances students’ understanding, and improves overall academic performance. These findings suggest educational institutions should consider integrating constructivist approaches to promote deeper learning and greater student success.